Synthesis of single-phase metal oxycarbonitride ceramics. (February 2020) - Li, Fei; Bao, Weichao; Sun, Shi-Kuan; Zhou, Lin; Liu, Ji-Xuan; Xu, Fangfang; Zhang, Guo-Jun
Abstract: Single-phase titanium-zirconium oxycarbonitride ceramics, prototypically Ti1/2 Zr1/2 (C1/3 N1/3 O1/3 ), was obtained by spark plasma sintering of the corresponding Ti and Zr- oxide, carbide and nitride. It was revealed that a single-phase Ti1/2 Zr1/2 (C1/3 N1/3 O1/3 ) solid solution with rock-salt structure formed at 2000 °C, below which the secondary phase of ZrO2 was evident. The as-sintered ceramics was chemically homogeneous from nanoscale to microscale and the carbon, nitrogen, and oxygen contents in Ti1/2 Zr1/2 (C1/3 N1/3 O1/3 ) ceramics were determined to be 5.39 wt%, 5.44 wt% and 6.00 wt%, corresponding to an empirical formula of Ti0.51 Zr0.49 (C0.37 N0.32 O0.31 ). The product possesses a relative density of 95.2% and Vickers hardness of 21.6 ± 2.4 GPa. Graphical abstract: Image, graphical abstract